Role of Survivin as a Diagnostic Tool for Oral Squamous Cell Carcinoma - Maryam, Hoor (International Journal of Pathology, 2022)
Introduction: Oral cancer is among the 10 most common malignancies in the world, about 90% of the oral malignant cancers are oral squamous cell carcinomas (OSCC). Survivin is the recently identified inhibitor of apoptosis protein (IAP). It has a dual function both in cell cycle promotion and apoptosis inhibition. Objectives: To assess the immuno-histochemical expression of Survivin in oral squamous cell carcinoma and normal oral mucosa. Material and methods: The study consisted of 30 diagnosed cases of OSCC, and 30 cases of normal healthy oral mucosa as a control. Immuno-histochemical expression of Survivin was analyzed. Results: Survivin showed positive immunoreactivity in all cases of OSCC (100%) but was absent in normal oral mucosa. Conclusion: Survivin expression was higher in oral squamous cell carcinoma, indicating that it could be used as a diagnostic marker for OSCC.